EDUCATIONAL MOVEMENT IN THE CAMP OF UKRAINIAN PRISONERS OF WAR FREISTADT, AUSTRIA-HUNGARY, 1915-1917 - Sribnyak, Ihor (Educological discourse, 2022)
The article reveals the peculiarities of the development of the educational movement in the camp of captured Ukrainian soldiers Freistadt (Austria-Hungary) in 1915-1917. It was established that despite all the initial difficulties (due to the opposition of the Black Hundreds) due to the systematic work of members of the Education Department, the Education Section Social and educational circle, the Society «Prosvita» M. Drahomanov during 1915-1917 it became possible to organize the teaching of a fairly wide range of courses and literacy schools (for the illiterate). The decisive role in the organization of educational life was initially played by the Union for the Liberation of Ukraine Educational Department, which included Ukrainian public figures, educators, cooperators with university or high school education, who had developed a national worldview. Through their efforts, the Ukrainian camp organization in Freistadt created appropriate structures from among the prisoners (educational section and the Enlightenment Society), which over time took over the main burden of educational work. Its content differed significantly – if at first the emphasis was on general education courses (so as not to provoke criticism of «politics» from prisoners), then within a year educational institutions paid more and more attention to Ukrainian studies (history of Ukraine, Ukrainian language and history of Ukrainian literature). At the same time, a large number of training hours were devoted to the elimination of illiteracy among prisoners. For many prisoners, education became the meaning of their camp life, and at the same time their national awareness took place, when they – sometimes even unnoticed – began to worry about the problems of Ukraine’s self-affirmation in political terms and became adherents of its independence. Thus, on the one hand, educational organizations purposefully prepared prisoners for the future of civilian life in the homeland, and on the other - to educate them conscious and loyal citizens of free Ukraine.